Connecting the dots: contributions to the creative tourism dynamics in Portugal - Cruz, A. R. (2019)
Drawing upon the implementation of an incubator and multidisciplinary collaborative research initiative – the CREATOUR project – which aims to develop a network of creative tourism initiatives in four Portuguese regions, the main purpose of this paper is to analyze the dynamics seen in the first stage of implementation of this network, trying to understand the relations and connections that have been established between the creative tourism actors operating at regional and national levels, and examining the main goals and challenges these particular actors face to implement such activities in small cities and rural areas of Portugal. Applying the methodological tools of Stakeholder Analysis and Social Network Analysis to the information collected from each of the 20 pilots involved in this stage of the project, the relationships between the various creative tourism pilot projects and other regional/external actors are represented and the stakeholders’ expectations regarding future developments of the network are analyzed.